Crystallization and preliminary X-ray diffraction analysis of haloalkane dehalogenase LinB from Sphingomonas paucimobilis UT26 - Smatanová, I; Nagata, Y; Svensson, L A; Takagi, M; Marek, J (Acta crystallographica. Section D, Biological crystallography, 1999)
Haloalkane hydrolytic dehalogenase LinB from Sphingomonas paucimobilis UT26, an enzyme which releases chloride or bromide anion from n-halogenated alkanes and has a broad range of substrate specificity, was crystallized using the hanging-drop vapour-diffusion method at 278 K. The best crystals were obtained by microseeding with a precipitant containing 18-20%(w/v) PEG 6000, 0.2 M calcium acetate and 0.1 M Tris-HCl pH 8.9. The crystals diffract to at least 1.60 A using synchrotron X-ray under cryogenic (100 K) conditions. They belong to the orthorhombic space group P21212 with unit-cell parameters a = 50.29, b = 71.70, c = 72.73 A. The asymmetric unit contains one molecule of the enzyme.
Keywords: Crystallography, X-Ray; Pseudomonas; Protein Conformation; krystalografie rentgenová; Hydrolases; Crystallization; konformace proteinů; krystalizace; hydrolasy